2012
DOI: 10.5194/nhess-12-3377-2012
|View full text |Cite
|
Sign up to set email alerts
|

Large historical eruptions at subaerial mud volcanoes, Italy

Abstract: Abstract. Active mud volcanoes in the northern Apennines, Italy, currently have gentle eruptions. There are, however, historical accounts of violent eruptions and outbursts. Evidence for large past eruptions is also recorded by large decimeter rock clasts preserved in erupted mud. We measured the rheological properties of mud currently being erupted in order to evaluate the conditions needed to transport such large clasts to the surface. The mud is wellcharacterized by the Herschel-Bulkley model, with yield st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…All samples show a unimodal distribution with mode ranging between 25 and 10 microns, similar to other mud volcanoes (e.g. Manga and Bonini, 2012); these clay particles largely derive from Holocene clays present at -20 to -40 m below ground level (Fig. 2).…”
Section: Characteristics and Flow Rates Of The Erupted Mudmentioning
confidence: 95%
“…All samples show a unimodal distribution with mode ranging between 25 and 10 microns, similar to other mud volcanoes (e.g. Manga and Bonini, 2012); these clay particles largely derive from Holocene clays present at -20 to -40 m below ground level (Fig. 2).…”
Section: Characteristics and Flow Rates Of The Erupted Mudmentioning
confidence: 95%
“…Interestingly, mud outcomes also occurred outside the subsided area that is thought to limit the mud volcanic caldera (Bonini 2008). Manga & Bonini (2012) report that the Regnano and Puianello mud volcanic centres, NW and SE of NMVF, respectively, as well as the NMVF responded to the strongest aftershocks of the Emilia seismic sequence with vigorous mud emissions. Furthermore, local foresters confirmed that the activity of the NMVF was particularly intense before the main shock of the Emilia sequence in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A common observation is that the complexity of the material composition and the effective rheological characteristics play important roles in material movement (Malet et al, 2003;Bisantino et al, 2010;Jeong, 2014;de Haas et al, 2015). This flow complexity is illustrated by the classification of subaqueous mass movements by Locat and Lee (2002) into five types with different behaviors: slides, topples, spreads, falls, and flows.…”
mentioning
confidence: 99%
“…Parameterized non-Newtonian fluid models are an obvious approach to approximate these behaviors. Timeindependent rheological models have been widely used to simulate debris flows (e.g., Bovet et al, 2010;Pirulli, 2010;Tsai et al, 2011;Manga and Bonini, 2012); however the realworld flow characteristics include time-dependent behaviors that could be categorized as "thixotropic" (Perret et al, 1996;Crosta and Dal Negro, 2003;Bagdassarov and Pinkerton, 2004;Aziz et al, 2010). Our focus in this paper is examining how a thixotropic model behavior compares to the more common time-independent (Herschel-Bulkley) non-Newtonian fluid model.…”
mentioning
confidence: 99%
See 1 more Smart Citation